Horizontal learning in the High Middle Ages : peer-to-peer knowledge transfer in religious communities - Long, Micol; Snijders, Tjamke, 1981-; Vanderputten, Steven (Knowledge communities (Amsterdam, Netherlands), 2019)
The history of medieval learning has been studied both as a vertical master-student phenomenon, and as part of a broad 'educational environment'. This volume centers on the ways in which cohabiting peers learned and taught one another in a dialectical process - how they acquired knowledge and skills, but also how they developed concepts, beliefs, and adapted their behavior to suit the group: everything that could mold a person into an efficient member of the community. This process of 'horizontal learning' emerges as an important aspect of the medieval learning experience.